Measurement of SUVs-Maximum for Normal Region Using VOI in PET/MRI and PET/CT - Jeong Kyu Park; Sung Kyu Kim; Ihn Ho Cho; Eun Jung Kong (The Scientific World Journal)
The purpose of this research is to establish an overall data set associated with the VOI (Volume of Interest), which is available for simultaneous assessment of PET/MRI and PET/CT regardless of the use of contrast media. The participants as objects of this investigation are 26 healthy examinees in Korea, SUV (standardized-uptake-value)s-maximum evaluation for whole-body F-18 FDG (fluorodeoxyglucose) PET/MRI image using VOI of normal region has exhibited very significant difference to that for whole-body F-18 FDG PET/CT image (significant probability value (P)<0.0001). However, there appeared high correlation between them in view of statistics (R-square (R)>0.8). It is shown that one needs to decide SUVs-maximum for PET/MRI with the reduction of 25.0~26.4% from their evaluated value and needs to decide with the reduction of 28.8~29.4% in the same situation but with the use of contrast media. The use of SUVLBM-maximum (SUVLean Body Mass-maximum) is very advantageous in reading overall image of PET/CT and PET/MRI to medical doctors and researchers, if we consider its convenience and efficiency. We expect that this research enhances the level of the early stage accurate diagnosis with whole-body images of PET/MRI and PET/CT.